A Review on Collar Rot Disease of Soybean Caused by Sclerotium rolfsii Sacc. - Bhamra, Gurpreet Kaur; Borah, Munmi (International Journal of Economic Plants, 2022)
Soybean (Glycine max (L.) Merrill) is high value legume oilseed crop grown throughout world as well as India. The crop is gaining popularity as it is an excellent source of vegetable protein (40-42% protein and 20-22% edible oil on dry weight basis). Collar rot disease caused by Sclerotium rolfsii Sacc. is a major constraint in soybean production leading to substantial yield losses. Favourable environmental conditions are indispensable for any plant disease in addition to the virulence of pathogen, age and susceptibility of host, date of planting and survival ability. It is also important in order to forecast the occurrence of disease and in devising management practices. Analysis of weather parameters provides a base to take pre- emptive decision against the disease under a given set of environmental conditions for better management practices. Keeping these points in view, the present review has attempted to compile findings on collar rot disease of soybean, the pathogen associated with it, symptoms, mode of spread, disease cycle, strategies on integrated disease management and influence of weather parameters on occurrence of the disease.